ANALISIS ESTIMASI BIAYA PERAWATAN BANGUNAN GEDUNG DI UNIVERSITAS PALANGKA RAYA - Pia Inez Devina; Rudi Waluyo; Veronika Happy Puspasari (Jurnal Teknik Sipil, 2023)
Building holds significant importance for the college to facilitate learning activities. Over time, buildings deteriorate and require regular maintenance to ensure their functionality and reliability. The aim of this study is to identify the type of damage, determine the percentage of damage to building components, and estimate the cost of maintenance for the buildings at Universitas Palangka Raya. Data collection involves conducting surveys and documentation. The analysis includes identifying damage to building components, calculating the volume of damage and total volume of building components, determining the percentage of damaged building components, and analyzing the cost of maintenance. The study reveals that out of 12 buildings at Universitas Palangka Raya, 13 types of architectural damage were found in various building sub-components. These include 0.526% of loose roof covering, 3.597% of fragile/eroded ceiling frame, 3.118% of fragile/damaged ceiling, 3.688% of the loose panel, 1.837% of cracked aluminum window glass, 58.594% of lost and damaged wooden door, 43.403% of lost and damaged planting key, 23.750% of the lost hinge, 3.725% of broken and cracked ceramic floor covering, 100% of cracked and loose concrete floor covering, 100% of rusty roof construction, and 0.769% of loose column pole cover sub-components. The total cost of maintenance is estimated to be IDR 207,463,000.